The Correlation Between Indoor Air Pollution with the Incident of Toddlerâs Pneumonia - Mahalastri, Ni Nyoman Dayu (Faculty of Public Health, 2014)
ABSTRACTPneumonia is a serious health problem in the world, including in Indonesia. Based on the results of Riskesdas 2007, pneumonia was the second ranking cause of death in the proportion of children aged 1â4 years and is under the diarrhea which ranks first. Environmental factors or conditions of the house, especially the air quality in the house is said to be one of the factors that can trigger pneumonia in infants. This study was conducted to determine the correlation of indoor air quality factors with the incidence of toddlerâs pneumonia. Type of this study is observational analytic and use case control design. The population of case group was all toddlers who become visitors Mojo Health Center in January 2014 until March 2014 and was diagnosed with pneumonia. While population of control group was all toddlers who become visitors Mojo Health Center in January 2014 until March 2014 and was diagnosed with diseases other than pneumonia. The number of respondents in this study were 60 respondents. The selection of the sample with simple random sampling method. The variables studied were cigarette smoke exposure in the house, size of ventilation and residential density. The results of the analysis using Epi Info StatCalc indicate that exposure to cigarette smoke in the house (OR = 4.00), size of ventilation (OR = 4.03), and residential density (OR = 4.38) has an correlation with incidence of toddlerâs pneumonia. It is expected that the public can avoid air pollution in the house in order to prevent toddlers from pneumonia.Keywords: cigarette smoke, size of ventilation, residential density, air quality, Â Â Â Â Â Â Â Â toddlerâs Pneumonia